Comparison of Plethysmographic and Helium Dilution Lung Volumes: Which Is Best for COPD? - O’Donnell, Carl R. (American College of Chest Physicians, 2010)
BACKGROUND: Theoretical considerations and limited scientific evidence suggest that whole-body plethysmography overestimates lung volume in patients with severe airflow obstruction. We sought to compare plethysmography (Pleth)-, helium dilution (He)- and CT scan-derived lung volume measurements in a sample containing many patients with severe airflow obstruction. METHODS: We measured total lung capacity (TLC) in 132 patients at three hospitals, with monitored application of recommended techniques for Pleth and He measurements of lung volume and by thoracic CT scans obtained during breath hold at full inspiration. RESULTS: Average TLC among 132 subjects was 6.18 L (± 1.69 L) by Pleth-derived TLC, 5.55 L (± 1.39 L) by He-derived TLC, and 5.31 L (± 1.47) by CT scan-derived TLC. Pleth-derived TLC was significantly greater than either He-derived TLC or CT scan-derived TLC (P ≤ .001), whereas there was no significant difference between He-derived and CT scan-derived values. When examined separately, there were significant within-subject differences in TLC by measurement technique among subjects with airflow obstruction, but not among those without airflow obstruction. Plethysmographic overestimation of TLC was greatest among subjects with FEV(1) < 30% of predicted. CONCLUSIONS: In the setting of airflow obstruction, Pleth systematically overestimates lung volume relative to He or thoracic imaging despite adherence to current recommendations for proper measurement technique.